Frontal assessment battery for detecting executive dysfunction in amyotrophic lateral sclerosis without dementia: a retrospective observational study. Issue 9 (3rd September 2015) - Barulli, Maria Rosaria; Fontana, Andrea; Panza, Francesco; Copetti, Massimiliano; Bruno, Stefania; Tursi, Marianna; Iurillo, Annalisa; Tortelli, Rosanna; Capozzo, Rosa; Simone, Isabella Laura; Logroscino, Giancarlo
Abstract : Objective: The frontal assessment battery (FAB) is a quick and reliable method of screening to evaluate frontal lobe dysfunction in amyotrophic lateral sclerosis (ALS). However, previous studies were generally conducted on small samples representing different stages of disease and severity. We assessed the diagnostic accuracy of the FAB in detecting executive functions and its association with demographic and clinical features in ALS without dementia. Design: Retrospective observational study. Setting: A multidisciplinary tertiary centre for motor neuron disease. Participants: We enrolled 95 consecutive patients with ALS diagnosed with El Escorial criteria in the period between January 2006 and December 2010. Main outcome measures: We screened the patients with ALS using the FAB. An Executive Index (EI) was also calculated by averaging the Z scores of analytic executive tests evaluating information-processing speed (Symbol Digit Modalities Test—Oral version), selective attention (Stroop test) and semantic memory (Verbal Fluency Test). Results: The FAB detected executive dysfunction in 13.7% of the patients with ALS. Moreover, using the EI standardised cut-off, 37.9% of the patients with ALS showed executive dysfunction. The receiver-operating characteristic curve showed that the optimal cut-off for the FAB in the whole sample was 16, with a sensitivity of 0.889 (95% CIs 0.545 to 1.000), a specificity of 0.593 (95% CI 0.450 to 0.907) and a moderate overall discriminatory power of 0.809. Different levels of respiratory function, duration of disease and depressive symptoms did not affect the FAB validity. Conclusions: In patients with ALS without dementia, a high prevalence of executive dysfunction was present. The FAB showed good validity as a screening instrument to detect executive dysfunction in these patients and may be used when a complete neuropsychological assessment is not possible.